Allegorical procedures updated: Artistic practice in post-media culture. Issue 2 (1st December 2014) - Wójtowicz, Ewa
Since contemporary culture is increasingly becoming the navigation culture, replacing the narrative culture, artists explore existing content and relate to its overproduction. An artist, as a semionaut, always relates to an external framework (conceptual, cultural or technological). In this article, I approach two theoretical frameworks – one by Benjamin Buchloh and another by Nicolas Bourriaud – and confront each with the latest examples of artistic re-practices in the online and the offline world. What was already present in the notion of allegorical procedure may be relevant again within the practice of postproduction. The whole range of artistic re-practices (e.g. remixes, remediations, and re-enactments) leads to a non-linear idea of time. Since the information is of greater importance than the visual representation, there is no centralized knowledge, but rather fragments to navigate between and a constant tension between the updated and the outdated.